1998
DOI: 10.1300/j052v17n04_02
|View full text |Cite
|
Sign up to set email alerts
|

Food Practices, Service Use, and Dietary Quality in Elderly Blacks

Abstract: Nutrient intake, food practices, service use, and their relationship to dietary quality in black elderly is described. A health and food questionnaire and three 24-hour food recalls were administered. Diets were very low in energy, calcium and vitamin B-6, slightly low in protein, thiamin, riboflavin and iron, and adequate in vitamins A, C and niacin. Men consumed more energy, fat, and cholesterol than women, and less vitamins C , B-6 and thiamin. Food stamps and home health aides (HHAs) were used more than ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…A number of factors predispose women to a higher risk of nutritional problems compared with men (Fogler-Levitt et al, 1995;Murphy et al, 1990), which may explain part of this phenomenon. Also, several studies have shown that older Black females have more nutritional inadequacies than Black males although a few studies have shown that Black females have higher quality diets than Black males (Cohen et al, 1998;Center for Nutrition Policy and Promotion, 1998). Further explanation may be the general tendency for women to be more health-conscious, that is, to report more symptoms and to visit doctors more frequently (Kearney, Kelly and Gibney, 1998;Ross et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…A number of factors predispose women to a higher risk of nutritional problems compared with men (Fogler-Levitt et al, 1995;Murphy et al, 1990), which may explain part of this phenomenon. Also, several studies have shown that older Black females have more nutritional inadequacies than Black males although a few studies have shown that Black females have higher quality diets than Black males (Cohen et al, 1998;Center for Nutrition Policy and Promotion, 1998). Further explanation may be the general tendency for women to be more health-conscious, that is, to report more symptoms and to visit doctors more frequently (Kearney, Kelly and Gibney, 1998;Ross et al, 1998).…”
Section: Discussionmentioning
confidence: 99%